A Critical Analysis of Performance Measures of Mutual Funds: A Comprehensive Analysis of Performance Measures in the Mutual Fund Industry (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The Mutual Fund industry today, with about 44 players and more than two thousand and five hundred schemes, is one of the most preferred investment avenues in India. However, with a plethora of schemes to choose from, the retail investor faces problems in selecting funds. Factors such as investment strategy and management style are qualitative, but the funds' record is an important indicator too. Though past performance alone cannot be indicative of future performance, it is, frankly, the only quantitative way to judge how good a fund is at present. Therefore, there is a need to correctly assess the past performance of different mutual funds. In this context, various tools used for measuring various mutual funds schemes and their units have been critically analyzed. I have made a humble attempt to critically analyze various measures used for the performance of schemes. Readers will understand that different measures will give different results based on the risk-return characteristics of various schemes.